ANALISIS HUKUM MENGENAI TATA KELOLA PAJAK BUMI DAN BANGUNAN PERKOTAAN DAN PERDESAAN DALAM RANGKA PEMBANGUNAN DAN KESEJAHTERAAN MASYARAKAT DESA - Nanak , Nanak Sukron; Endeh Suhartini; Abraham Yazdi Martin; Asep Thobibudin Qolyubi (JURNAL ILMIAH LIVING LAW, 2024)
This study aims to learn about and analyze legal studies on rural and urban land governance and building tax in the context of development and well-being of rural communities and to know the role of information technology in the management of rural and urban areas of the United Nations in order to improve community obedience and discipline of the tax system. The method used is to make the field of legal science the foundation of its mother science, so the research used is normative legal research. The results showed that the Rural and Urban Property and Construction Tax (PBB-P2) should be collected on the basis of laws and regulations from the top to the implementing regulations, namely village regulations and information technology optimization, as it plays an important role in the management of the Rural and Urban Property and Real Estate Tax (PBB-P2). In terms of increased public obedience, information technology can be used to facilitate and speed up the tax payment process. For this reason, it is important to guide UN-P2 governance to village governments on the basis of fair and transparent legal principles, in order to foster the development and well-being of rural communities.